Hollow nanoporous covalent triazine frameworks via acid vapor-assisted solid phase synthesis for enhanced visible light photoactivity. Issue 20 (26th April 2016) - Huang, Wei; Wang, Zi Jun; Ma, Beatriz Chiyin; Ghasimi, Saman; Gehrig, Dominik; Laquai, Frédéric; Landfester, Katharina; Zhang, Kai A. I.
Abstract : Herein, we report a novel trifluoromethanesulfonic acid vapor-assisted solid phase synthetic method to construct nanoporous covalent triazine frameworks with highly ordered hollow interconnected pores under mild reaction conditions. Abstract : Herein, we report a novel trifluoromethanesulfonic acid vapor-assisted solid phase synthetic method to construct nanoporous covalent triazine frameworks with highly ordered hollow interconnected pores under mild reaction conditions. This unique solid state synthetic route allows not only the avoidance of undesired side reactions caused by traditional high temperature synthesis, but also the maintaining of defined and precise optical and electronic properties of the nonporous triazine frameworks. Promising photocatalytic activity of the polytriazine networks was demonstrated in the photoreduction reaction of 4-nitrophenol into 4-aminophenol under visible light irradiation.